PANDANGAN HUKUM POSITIF DAN HUKUM ISLAM TERHADAP PEMBAGIAN HARTA GONO-GINI - Usman Alfarisi; Zainul Fikri; Risidianto (Universitas Darunnajah Jakarta, Indonesia, 2023)
This research aims to explain the views of Islamic Law and Positive Law regarding the division of Gono-gini Property. This research uses a normative legal approach method. Where this research is descriptive-analytical-comparative, meaning that the author will describe how the division of Gono-gini Property in the perspective of Islamic Law and Positive Law. The results showed that the division of Gono-gini Property in the perspective of Islamic Law and Positive Law that the division of joint property in the view of Islamic law and positive law is in accordance in general divided equally between husband and wife. In the perspective of Islamic Law, if the division of joint property in the event of a divorced married couple prioritizes the method of peace (deliberation). Based on this view, actually joint property can be traced in Islamic law, both through the concept of shirkah and based on the will of Islamic law itself using KHI Article 97, the division of one-half for husband and wife. While in the perspective of positive law this is based on Law No. 1 of 1974 article 37 and Civil Code articles 128-129 that if the breakup of the marriage rope between husband and wife, then the joint property is divided in half between husband and wife. However, in the above law, as long as the parties do not determine otherwise, it is regulated according to their respective laws.